Facile thermoplastic polyurethane-based multi-walled carbon nanotube ink for fabrication of screen-printed fabric electrodes of wearable e-textiles with high adhesion and resistance stability under large deformation. Issue 21 (November 2021) - Jiang, Lihong; Hong, Hong; Hu, Jiyong
Carbon nanotubes have been widely used to formulate printed conductive ink in recent years due to their excellent conductivity, chemical stability and mechanical properties. However, the common problems of this ink, such as poor adhesion and low resistance stability under large deformation, hinder its application in the fabric electrodes (FEs) of wearable and stretchable e-textiles. Herein, conductive inks with a simple preparation process, high adhesion and conductive stability were formulated by mixing the conductive filler, multi-walled carbon nanotubes (MWCNTs), into a thermoplastic polyurethane matrix with a reversible cross-linked structure. Then it is evaluated whether the MWCNT-based conductive ink is suitable for the screen-printing fabrication of highly durable and washable FEs. The experimental results showed that the screen-printed fabric electrode exhibited remarkable resistance stability under bending and folding deformation. In particular, after 1000 bending cycles and 100 folding–unfolding cycles under additional pressure, the sheet resistance of FEs only increased by 0.8% and 5.0%, respectively. Moreover, the screen-printed conductive pattern has strong adhesion to polyamide fabric substrate by the Scotch tape and washing tests, and there are no significant changes in resistance and surface morphology. High-performance conductive inks with facile and large-scale production potential are developed, and show great prospect in the development of wearable printing e-textiles.